Experimental study of seismic behavior Of scaled non-engineered masonry Structures retrofitted by pp-band mesh - Nazir, S.; Sathiparan, N.; Numada, M.; Meguro, K. (My University, 2010)
Most residential structures in developing countries are masonry structures which are highly vulnerable to earthquake and increase the structural damage and the death toll. This paper discusses the seismic capacity of non-engineered common masonry structures in Pakistan, which having more tendency to collapse due large weight of slab, by experimental approach using 1/12 miniature models. These models were constructed using acryl blocks which can be used several times. This paper also includes the comparison of retrofitted masonry model by PP-band, a method proposed by Meguro Laboratory, IIS, the University of Tokyo, with non-retrofitted one. The PP-band retrofitted masonry model showed almost 4 and 16 times greater seismic capacity than the non-retrofitted one in terms of ground acceleration and arias intensity, respectively.
Keywords: Masonry structure; seismic retrofitting